Insect mediated bioconversion in the circular bioeconomy: evaluation of quality, safety and environmental impact - Rossi, Giacomo; Justus Liebig University Giessen (My University, 2024)
Industrially farmed insects are receiving increasing attention within the modern bioeconomy. Due to a diverse range of microorganisms living in their gut, insects are able to grow on biological waste and by-products, recover nutrients and produce new high-quality materials to be exploited within the agriculture, food, feed, medical and industrial sectors. Their high adaptability to different conditions, along with their limited production of greenhouse gasses, low use of resources, high feed conversion and valuable nutritional profile, has also suggested them as potential food and feed sources for the future. However, despite such interesting properties, legislative limitations, often led by fragmented and contradictory knowledge or lack of data, appear to be a serious limitation for their affirmation in the circular bioeconomy. This thesis focuses on the evaluation of quality, safety and environmental impact of edible insects produced by applying circular economy concepts. Chapter 1 defines the overall background knowledge motivating the performed experiments. It offers an overview of the research gaps that form the basis for the experimental work and describes the overall structure of the thesis. A general introduction covering several aspects concerning the use of insects in the circular bioeconomy, with a specific focus on insects as waste management tool and as future food and feed is summarised in Chapter 2. Chapter 3 represents the core of the thesis. Six experiments, carried out with the aim of answering the research questions defined in Chapter 1 and addressing the identified research gaps are presented and discussed. Specifically, section 3.1 focuses on the development of a new, non-destructive optical system for the rapid monitoring of quality changes of edible insect products. Fluorescence spectra of dry insect powders, produced by milling insects of five different species belonging to the Orthoptera order, were recorded. The 3D data were organised into an Excitation Emission Matrix (EEM) and analysed through machine learning tools. Five independent fluorescence peaks, each resulting from a different class of chemical compounds, were identified. The obtained results were therefore further applied to detect the oxidation status of insect paste subjected to high hydrostatic pressure (HHP) processing (section 3.2). Two experiments were conducted by applying HHP to insect paste at 600 MPa for 5 min. In the first experiment (experiment 2.1), three modified atmosphere packaging (MAP) and normal air packaging were applied after HHP treatment and microbial load as well as lipid and protein oxidation status were monitored during 28 days of refrigerated storage. Results suggested that the combination of HHP with oxygen-free MAP allowed shelf-life extension up to 10 days when refrigeration was applied. However, HHP treatment was found to be responsible for oxidation initialisation. Therefore, the second experiment (experiment 2.2) aimed to validate such observation and test whether addition of commercial antioxidant mixtures before applying HHP could delay the oxidation process. Results showed that although antioxidants exhibited their activity differently during the storage (with the synthetic antioxidant being more active in the initial stage of the storage while the natural antioxidant being more active in a later stage), HHP alone was not responsible for any significant oxidation. Considering the most interesting aspect of edible insects regarding waste conversion, section 3.3 investigates the possibility of using black soldier fly larvae (BSFL) as a tool for managing waste from aquaculture production (ASW). Two experiments, the first using fresh (daily-collected) ASW and the second applying anaerobically digested (bulk-accumulated) ASW, were therefore carried out. The first experiment (experiment 3.1) demonstrated that BSFL can conveniently convert ASW; however, the high water content of the initial material required the inclusion of other ingredients in the diet. Mixtures consisting of 75% ASW and 25% of chicken feed were found to be optimal for supporting larval growth and waste conversion. However, the amount of nutrients assimilated by the larvae was extremely low, indicating a significant loss of nutrients. High nutrients retention and consequently a low environmental impact was observed in substrate 100ASW, which was characterised by low dry matter content, resulting in feed limitation for the BSFL. These results were further confirmed in the second experiment (experiment 3.2), which showed that conditions leading to high larval growth performances were negatively correlated with the reduction of environmental impact. Furthermore, experiment 3.2 also displayed low growth ability of BSFL on bulk accumulated ASW, indicating that fresh ASW should be preferred for insect-mediated aquaculture waste conversion processes. However, although these two experiments showed low nutrient retention by BSFL reared under optimal conditions, the actual amounts of nutrients lost by the larvae in form of gas were not quantified. Therefore, in order to accurately quantify the gas emissions from edible insects during the rearing process, a new open dynamic gas emission chamber was designed and validated for monitoring the greenhouse gas (GHG) emissions from edible insects on a small scale (section 3.4). Validation experiment was carried out by rearing BSFL on moistened chicken feed. Obtained results showed that BSFL produced neither CH4 nor N2O, while CO2 production strictly depended on insect growth and metabolic activity. Accordingly, CO2 emission curves closely resembled the larval growth curves, indicating that an accurate estimation of GHG emission from insects should consider the overall life cycle of the insect, from eggs to harvesting stage, including the neonate stage. Based on the obtained results, an overall conclusion highlighting the main findings and addressing the research questions defined at the beginning of the thesis is presented in the final chapter (Chapter 4). Relevance of the overall thesis within the circular bioeconomy framework and the future steps needed to promote a full transition to the circular bioeconomy, are also illustrated in this chapter.
Keywords: ddc:630